Host-Associated Distribution of Two Novel Mammarenaviruses in Rodents from Southern Africa - Geldenhuys, Marike; Weyer, Jacqueline; Kearney, Teresa; Markotter, Wanda (Viruses, 2022)
Mammarenaviruses are hosted by several rodent species, a small number of which have been known to be zoonotic. Host surveillance among small mammals has identified a large diversity of previously undescribed mammarenaviruses. Intensified biosurveillance is warranted to better understand the diversity of these agents. Longitudinal host surveillance involving non-volant small mammals at a site in the Limpopo province, South Africa, was conducted. The study reports on the screening results of 563 samples for the presence of mammarenavirus RNA. PCR-positive samples were subjected to sequencing using Miseq amplicon sequencing. Sequences with close similarity to Mariental and Lunk viruses were identified from two rodent species, Micaelamys namaquensis and Mus minutoides. This represents the first description of these viruses from South Africa. The genomic sequences reported here partially satisfied the requirements put forward by the International Committee on the Taxonomy of Viruses’ criteria for species delineation, suggesting that these may be new strains of existing species. The known distribution of these mammarenaviruses is thus expanded further south in Africa.